Control of total cholesterol in pharmacy patients using artichoke extract (Cynara scolymus) - Lima, Lívia de Toledo (2023)
Cholesterol is synthesized by the liver and acquired through food. However, excess LDL (low-density lipoprotein) in the bloodstream can form atherosclerotic plaques and clog vessels and capillaries. The Cynara scolymus (Artichoke) plant can act as an antiatherosclerotic, lowering blood cholesterol levels. Thus, the objective of this work was to carry out a survey on the main factors related to cholesterol levels and to analyze the effect of the use of Cynara scolymus extract in relation to hypercholesterolemia in patients at the Municipal Pharmacy of Ubá-MG. For this purpose, investigative questionnaires were applied to patients at the pharmacy to assess various factors related to cholesterol. A group of 20 people who claimed to have high cholesterol were selected to undergo blood tests and assess their cholesterol level. It was observed that 10 patients had high total cholesterol, and they were divided into two groups of 5 people: an experimental group, in which participants used Cynara scolymus extract and the other group medicated with placebo. After one month of medication consumption, there was greater oxidizing activity in patients in the artichoke group, reaching a decrease of up to 21% in cholesterol levels, compared to patients in the control group. Thus, the use of Cynara scolymus seems to help control plasma cholesterol.